Caracterização físico-química e estrutural de complexos amido-monoestearato de glicerol em amidos de cereais e a influência da β-ciclodextrina - Garcia, Marina Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Effect of β-cyclodextrin (βCD) in the formation of amylose-lipid and / or amylopectin-lipids complexes using glycerol monostearate (GMS) (1, 2, 3% w/w), and wheat, normal corn, waxy corn and high amylose starches were physicochemically and structurally evaluated in the presence or absence of β-cyclodextrin (βCD) (3% w/w). Normal corn and wheat starches were characterized by similar amylose content (~ 25%) and A-type X-ray pattern. High amylose corn starch (49.8%) presented the B-type crystalline pattern, whereas the waxy corn starch with A-type crystalline pattern had 1.1% of amylose. The higher lipid (0.75%) and phosphorus (0.05%) contents in wheat starch contributed to its lower gelatinization temperature. Addition of βCD in native starches suggested that this oligosaccharide interfered in the formation of amylose-lipid complexes naturally present in starches, more intensely in the wheat starch mainly due to their higher content and type of lipids. Addition of GMS reduced breakdown and setback in wheat, normal corn and waxy corn starches due to the retrogradation complications of the amylose and/or complexed amylopectin molecules. After the βCD addition, there was an increase of ΔHcx for wheat, normal corn, and high amylose corn starches, suggesting the amylose-GMS complex disruption by βCD and a possible association between βCD and GMS. The produced complexes of starches with GMS (1, 2 and 3%) disclosed faceted structures typical of crystals when observed by SEM and AFM, V-type crystalline pattern and endothermic peaks of dissociation between115 to 120 ° C, which classify them as IIb polymorphism. The results suggested that 1% of GMS was enough to complex with amylose and / or amylopectin molecules available for complexing in the wheat, normal corn, and waxy corn starches, whereas in the high amylose corn starch, concentrations below 3% GMS were not enough to saturate and complex all available amylose. The resistant starch ...

O efeito da β-ciclodextrina (βCD) na formação de complexos amilose-lipídios e/ou amilopectina-lipídios usando monoestearato de glicerol (GMS) (1, 2 e 3% m/m) e amidos de trigo, milho normal, milho ceroso e milho com alto teor de amilose foram estudados físico-química e estruturalmente na presença ou ausência de β-ciclodextrina (βCD) (3% m/m). Os amidos de trigo e milho normal se caracterizaram por apresentarem teores de amilose semelhantes (~ 25%) e padrão de raios-X tipo A. O amido de milho com alto teor de amilose (49,8%) apresentou padrão cristalino tipo B, enquanto o amido de milho ceroso, com padrão tipo A, teve 1,1% de amilose. O maior teor de lipídios (0,75%) e fósforo (0,05%) no amido de trigo contribuiu para sua menor temperatura de gelatinização. A adição de βCD nos amidos nativos interferiu na formação dos complexos amilose-lipídios presentes naturalmente nos amidos, de forma mais intensa no amido de trigo devido principalmente ao seu maior teor e tipo de lipídios. A adição de GMS reduziu a viscosidade de quebra e setback nos amidos de trigo, milho normal e milho ceroso devido à dificuldade de retrogradação das moléculas de amilose e/ou amilopectina complexadas. Após a adição da βCD, o ΔHcx aumentou para os amidos de trigo, milho normal e milho com alto teor de amilose, sugerindo o rompimento do complexo amilose-GMS pela βCD e associação entre βCD e GMS. Os complexos produzidos dos amidos com GMS (1, 2 e 3%) mostraram estruturas facetadas típicas de cristais quando observados em MEV e AFM, padrão cristalino tipo V e picos endotérmicos de dissociação entre a C, o que os classificou como complexos com polimorfismo IIb. Os resultados mostraram que 1% de GMS foi suficiente para complexar com as moléculas de amilose e/ou amilopectina disponíveis para complexação nos amidos de trigo, milho normal e milho ceroso, enquanto que no amido de milho com alto teor de amilose, concentrações abaixo ...
Keywords: Tecnologia de alimentos; Amido - Indústria; Beta-ciclodextrina; Amilose; Amides Industry